(untitled) (PAMPA, 2023)
This work consists of a case study analysis of the upper basin of the Cuñapirú stream, located in the department of Rivera, in the area known as Puntas de Cuñapirú, identifying environmental problems and issues related to territorial transformations in the period 1990-2017. It aims to provide elements for understanding the processes of territorial transformations over a period of 27 years. The application of an environmental vulnerability model that integrates fragility and threat factors makes it possible to identify areas that are particularly sensitive to current and future impacts and facilitates the identification of critical interactions in the environmental system, generating inputs for decision-makers. The application of the model was able to identify spatially the areas with the highest rate of urban expansion, which in turn constitutes the main threat and generates the highest levels of vulnerability. It was also possible to recognise which natural assets interact with these changes in land use (environmental fragility). It is hoped that the results obtained will help to strengthen land-use planning and management capacities.